Encyclopedia of Modern British Army - Gander, Terry (London Guild Publishing, 1986)
The present-day regiments of the British Army, many dating back to the seventeenth century, have long and distinguished histories. Campaigns in war and peace across the world, from Flanders to the North West Frontier and from Spain to New Zealand, are still celebrated in regimental customs and battle honors. Since the first edition of this book, there have been dramatic cuts in defense spending and comprehensive role changes for many of the Army's oldest regiments. A reappraisal of the make-up and traditions of the Army's basic building blocks, its regiments, is therefore timely. The regiments and corps of the British Army, many preserving traditional titles such as Dragoon Guards, Hussars, Lancers and Fusiliers, are considered in order of precedence. Details given for each regiment include insignia, battle honors, anniversaries, customs, mascots, dress distinctions, marches, nicknames, headquarters and recruiting areas. In addition, there is a 'family tree' for each regiment, showing its lineage since its original foundation. A wide selection of color and black & white pictures illustrate key moments in each regiment's history and its current activities across the globe.
Includes Colored Illustrations and Index.
Keywords: Great Britain. Army